A simple route for the synthesis of novel 1, 4-benzoxazine derivatives by Baeyer–Villiger oxidation reaction. Issue 29 (21st July 2016) - Ghanbari, Mohammad; Jadidi, Khosrow; Mehrdad, Morteza; Assempour, Nazanin
Abstract: Novel 1, 4-benzoxazine derivatives were synthesized by an efficient and simple method in high yields. Readily available starting materials, operational simplicity, mild reaction conditions and novelty are the key advantages of this method. The synthetically attractive feature of the procedure is reflected by its applicability to a wide range of isatin and aniline derivatives. Besides their novel structures, these compounds may have important biological activities and industrial applications. Furthermore, we demonstrated that in Baeyer–Villiger oxidation reaction, the phenyl group migrate better than amidine groups but not as good as amide group. The migratory ability for these groups in Baeyer–Villiger oxidation reaction is ranked amide > phenyl > amidine. Graphical abstract: